2009
DOI: 10.1213/ane.0b013e3181b0826a
|View full text |Cite
|
Sign up to set email alerts
|

Should Dosing of Rocuronium in Obese Patients Be Based on Ideal or Corrected Body Weight?

Abstract: In obese patients undergoing gastric banding or gastric bypass, rocuronium dosed according to IBW provided a shorter duration of action without a significantly prolonged onset time or compromised conditions for tracheal intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 24 publications
5
83
1
8
Order By: Relevance
“…13 Thus, as is the case for non-depolarizing muscle relaxants, it might be relevant to determine the dose of sugammadex based on the ideal body weight and not on the actual body weight. 14 The affinity of sugammadex for rocuronium is high, so unbinding of sugammadex-rocuronium complexes is unlikely. One molecule of sugammadex binds to one molecule of rocuronium or vecuronium.…”
Section: Discussionmentioning
confidence: 99%
“…13 Thus, as is the case for non-depolarizing muscle relaxants, it might be relevant to determine the dose of sugammadex based on the ideal body weight and not on the actual body weight. 14 The affinity of sugammadex for rocuronium is high, so unbinding of sugammadex-rocuronium complexes is unlikely. One molecule of sugammadex binds to one molecule of rocuronium or vecuronium.…”
Section: Discussionmentioning
confidence: 99%
“…Data are available to provide some guidance on appropriate dosing for common perioperative medications (Table 3). 64,65,[67][68][69][70][71][72][73][74] In Table 4, there is an outline of the calculation methods for the various dosing weights.…”
Section: Intraoperative Carementioning
confidence: 99%
“…4 Meyhoff et al reported that the dose of rocuronium should be calculated according to ideal body weight to prevent the prolonged rocuroniuminduced neuromuscular block in morbidly obese patients. 9 The findings of the present study suggest that the higher the BMI, the longer the duration of rocuronium-induced neuromuscular block, even in non-obese patients. Thus, even if the patient is not categorized as ''obese'' according to the WHO classification, the higher the BMI of the patient, the more carefully rocuronium should be administered with neuromuscular monitoring to prevent prolonging neuromuscular block.…”
Section: Discussionmentioning
confidence: 47%